ESports diplomacy: towards a sustainable 'gold rush'. Issue 8 (3rd August 2022) - Murray, Stuart; Birt, James; Blakemore, Scott
Abstract: With a marked growth in the industry of esports, this paper examines the epistemological, ethical and operational challenges impacting esports. In exploring the available literature on the esports phenomena, it argues that the current 'gold rush' is unsustainable unless the problems of government interference, legitimacy, regulation and inequality within gaming culture are tackled by widening the study of esports. To manage the challenges confronting esports and recognise the potential benefits, this paper proposes that the theory of sports diplomacy be applied to esports. Doing so provides a better framework for understanding and tackling the challenges threatening the growth and legitimacy of esports.